Situational Modeling of the Attitude to the People with Disabilities - Stavitsky, Oleg Alekseevich (Psychological Prospects Journal, 2012)
The article specifies the concepts of «handicapism», «handicap» and «handicapping». The empirical research analysis of handicaps manifestations as to the people with disabilities is conducting.
Keywords: handicapism handicap handicapping disability